Teaching Science Education with special reference to Morals, Values, Ethics, And Character Education. - IGIRI, CHARLES EGBONYI; ACHIGBE, JULIUS OGRI; EFFIONG, OJI EKPO (IJRDO- Journal of Educational Research, 2019)
This paper presents the rationale and arguments for the presence of morals, values, ethics and character education in science curriculum and science teaching. The author examines how rapid science and technological advancements and globalization are contributing to the complexities of social life and underpinning the importance of morals, values and ethics In order to help conceptualize and articulate a solid theoretical framework for the development of school programs, syntheses and analyses are presented to the philosophical and pedagogical questions related to morals, ethics and character education. Various obstacles in teaching morals/ethics and implementing character education in the sciences were discussed. A range of teaching, learning and pedagogical techniques are proposed that may foster morals, values and ethics in students’ minds and develop various skills and attributes necessary for success in the sciences.